Pengembangan Media Pecahan Berbasis Demonstrasi pada Pembelajaran Matematika di Sekolah Dasar Swasta Islam Ulul Albab Jember - Sofwan Roif Ubaidillah; Umi Farihah; Erma Fatmawati; Lailatul Usriyah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Mathematics learning in primary schools is often perceived as challenging and uninteresting by students, particularly in fraction topics that require strong visualization skills. This study aims to develop a demonstration-based fraction media designed to help students understand fraction concepts through concrete and interactive learning experiences. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, involving 25 third-grade students from SDS Islam Ulul Albab Jember. Data were collected through expert validation sheets, student response questionnaires, and pre-test and post-test assessments. The validation results showed average scores of 4.90 from media experts, 4.90 from material experts, and 4.50 from the classroom teacher, all falling under the “highly feasible” category. Student responses were also very positive, with an average score of 4.98. The effectiveness of the media was reflected in a substantial improvement in learning outcomes, with the average score increasing from 62.4 (pre-test) to 86.7 (post-test). These findings indicate that the demonstration-based fraction media is effective, engaging, and capable of enhancing students’ understanding of fraction concepts. Therefore, this media is recommended as an alternative instructional tool to support mathematics learning in primary schools, especially for topics that require visual and manipulative understanding.